Heterogeneous vascular patterns in renal cell carcinomas - Ferician, Ovidiu; Cimpean, Anca Maria; Ceausu, Amalia Raluca; Dema, Alis; Raica, Marius; Cumpanas, Alin (Polish Journal of Pathology, 2016)
The present study proposes a classification of renal cancer tumor blood vessels according to their morphology and maturation grade. We identified four vascular patterns: reticular, diffuse, fasciculated and trabecular. The reticular pattern was present in 63% of cases, being characterized by the predominance of mature CD34+/SMAct+ tumor vessels, highly interconnected. For this pattern, 74% of cases had vascular invasion, and a significant correlation was observed between tumor grade and immature state of tumor vessels (p = 0.022). The diffuse pattern was observed in 23% of cases and was characterized by non-interconnected vessels predominantly of mature CD34+/SMAct+ type and vascular invasion in 64% of cases. Only 8% of cases, had a fasciculate model of vessels distribution, all of them being of mature type, located in the connective axis of papillary renal tumors. For this pattern vascular invasion was found in 50% of cases. In 6% of cases a trabecular pattern was observed and the lowest rate of vascular invasion was registered. We defined here four distinct vascular patterns in renal cell carcinomas showing a strong impact on vascular invasion. A complete morphological and molecular characterization of tumor vessels would be beneficial in elucidating the mechanisms that underlie the ineffectiveness of antiangiogenic/antitumor therapies.